A Place for Spirituality - Worrell, Patricia (My University, 2005)
This article examines the justification for including a spiritual dimension in the planning of formal education programmes. It argues that the society needs to determine, once and for all, what it believes about the role of spiritual education in the lives of our children. If it is determined to be important, then the article suggests that educators will be required to approach the process of planning and implementing the curriculum in a way that recognizes human beings as spiritual beings
Keywords: Religious education; Spirituality; Trinidad and Tobago